The Effects of Cigarette Smoking on the Cardiovascular System: Mechanisms of Damage, Risk Factors, and Prevention Strategies - Janowska, Kinga; Szydziak, Joanna; Hrapkowicz, Aleksandra; Dąbkowska, Daria; Szeidl, Olga; Rehan, Dominika; Mioskowska, Agnieszka (Journal of Education, Health and Sport, 2025)
Introduction: Cardiovascular diseases remain the leading cause of morbidity and premature mortality. Even though the prevalence of cigarette smoking has decreased over the last few decades, it is still one of the most important preventable risk factors for cardiovascular diseases. Moreover, recently, an increasing number of people have been transitioning to e-cigarettes, which also influence blood pressure and the cardiovascular system. Purpose of the study: The following review analyzes the association between cigarette smoking and both prevalence and development of cardiovascular diseases. It also suggests the management of tobacco addiction. Materials and methods: A literature review of English language papers was conducted to summarize the latest knowledge on the topic, focusing on the most recent papers. The review was conducted using the PubMed database, with 53 works used and accessed before December 2024. Conclusions: Tobacco significantly affects the cardiovascular system, with numerous studies highlighting the negative impacts of both active and passive smoking. Although extensive knowledge exists about tobacco smoke’s impact on the cardiovascular system, further research is still needed. A better understanding of the link between smoking and the development of cardiovascular diseases, as well as methods for the management of the addiction, is crucial to developing successful treatment and prevention strategies.